MILLS’ PERSPECTIVE ON SIMA BAHOUS CLOSING SPEECH AT UN-WOMEN ANNUAL SEASON: A FEMINIST CRITICAL DISCOURSE ANALYSIS - Muthi'ah, Nadhirah; Frida, Karunia Devy; Zein, T. Thyrhaya (Universitas Islam Sumatera Utara (UISU), 2023)
The study aimed to find out the women's representation of Sima Bahous' speech entitled